Rancang Bangun Website Company Profile Berbasis Framework Boostrap dan Framework Codeigniter Pada Yayasan Khalifah Cendekia Mandiri - Ahmad Martani; Saripuddin M; Nurul Ikhsan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Khalifah Cendekia Mandiri Foundation is located in Moncongloe District, Maros Regency, South Sulawesi Province. Having problems in terms of delivering information that still uses conventional methods, including the delivery of information by placing banners and through bulletin boards and brochures which are felt to have many shortcomings, the reach of information dissemination is not wide enough, the information content is limited, the process of updating information is not profitable either regarding cost and time. The research method used in this research is the RAD (Rapid Application Development) method. From the research conducted, namely designing a Company Profile Website based on the Boostrap Framework and the CodeIgniter Framework using the CSS Bootstrap Framework interface design, it has produced a website application that can facilitate data and information management as well as a form of convenience for the public to access information.